Inhibitory effects of sildenafil citrate on the tonus of isolated dog internal anal sphincter - Aygen, E; Camci, C; Durmus, AS; Dogru, O; Topuz, O; Ayten, R; Ayar, A (Lippincott Williams & Wilkins, 2005)
PURPOSE: Although the exact pathogenesis of anal fissure is not known, hypertonicity of the internal anal sphincter might be involved in its pathogenesis as main event. To gain information about possible usefulness of the novel, smooth-muscle-relaxing drug, sildenafil, in chronic anal fissure, we investigated the effect of sildenafil citrate on acetylcholine-induced contractility of internal anal sphincter isolated from dogs. METHODS: Internal anal sphincter strips were taken from German shepherd clogs and suspended in a tissue bath filled with Krebs solution at 37 degrees C (pH 7.4) continuously bubbled with 95 percent oxygen and 5 percent carbon dioxide, and isometric contractions were recorded. Contractions were evoked by 10 mu M acetylcholine, and the effects of different concentrations of sildenafil citrate (0.1, 0.3, and 1 mM) on the isometric tension of each internal anal sphincter strip were examined. The statistical significance was analyzed by one-way analysis of variance. RESULTS: Pretreatment with sildenafil citrate (0.1 mM) attenuated contractile response to acetylcholine (n = 3), which were significantly weak compared with the maximum contractile response to the acetylcholine alone (610 +/- 110 mg vs. 2,825.17 +/- 416 mg; n = 12; P < 0.05). Sildenafil citrate also significantly inhibited the acetylcholine-induced contractions in a dose-dependent manner when applied after. CONCLUSIONS: This experimental in vitro study showed that sildenafil citrate relaxes acetylcholine stimulated contractions of isolated dog internal anal sphincter. This may be of importance for raising the possibility that sildenafil citrate may have future potential in the treatment of chronic anal fissure. Further studies are needed for a conclusive decision on possible usefulness of sildenafil citrate in patients with chronic anal fissure.
Cukurova Colo-Proctology Course and Symposium -- JUN 03-06, 2003 -- Adana, TURKEY
Keywords: internal anal sphincter; sildenafil citrate